Fight like a girl. The impact of menstruation on female athletes in combat sports - Elisa Virgili (Eracle. Journal of Sport and Social Sciences, 2025)
This paper aims to investigate the relationship between menstruation and sports, specifically from the perspective of women who play combat sports. Much of the research concerning sports, and the factors that affect sports performance, is based on a universal male subject. It does not take into account differences related to gender and sex. There is a male bias in the the assumption that a normal body is immutable and characterised by stability. Such a conception excludes the female body which undergoes cyclic changes on a monthly basis. Starting from this assumption, the aim of this paper is to see how female athletes deal with this norm. The study centers on the experiences of female athletes, spanning from their physical education during schooling to their current training and competitive activities. Employing the concept of menstruation as both a biological and socio-cultural factor, this work seeks to deconstruct the prevailing sports canon, revealing that the notion of neutrality often corresponds to male-centered neutrality.